(untitled) (Journal of Nobel Medical College, 2018)
Background: Acute appendicitis is very common surgical cause of acute abdomen and needs surgical removal either by laparoscopic or open appendicectomy. The aim of this study is to compare frequency of surgical site infection (SSI) in patients undergoing laparoscopic and open appendicectomy. Materials and Methods: The study was prospective study conducted in NMCTH, Biratnagar. Total 200 patients with diagnosis of acute appendicitis admitted through the emergency department of our hospital were included in the study. The patients were randomly allocated in two groups: Laparoscopic appendicectomy group (LA) and Open appendicectomy group (OA). Both groups underwent successful emergency appendicectomy. Wound infections in terms of surgical site infection (SSI) if present were recorded. All age groups and both sexes were included. Results: Two hundred patients underwent appendicectomy, one hundred Laparoscopic appendicectomy (LA) and another hundred open appendicectomy (OA). The mean age of patients with acute appendicitis was 30.63±16.14 years with minimum of 6 years and maximum of 77 years. The highest number of patients were in age group of 10 to 20 years (29.5%). In LA group SSI noted in 3 patients (3%) whereas in OA group it was found in 12 patients (12%). Conclusion: Laparoscopic appendicectomy is better and offers great advantages in terms of SSI as compared to Open appendicectomy.